Prefrontal Hypoactivity Associated with Impaired Inhibition in Stimulant-Dependent Individuals but Evidence for Hyperactivation in their Unaffected Siblings - Morein-Zamir, Sharon (Nature Publishing Group, 2013)
A neurocognitive endophenotype has been proposed for stimulant dependence, based on behavioral measures of inhibitory response control associated with white matter changes in the frontal cortex. This study investigated the functional neuroimaging correlates of inhibitory response control, as functional activity serves as a more dynamic measure than brain structure, allowing refinement of the suggested endophenotype. Stimulant-dependent individuals (SDIs), their unaffected siblings (SIBs), and healthy controls (CTs) performed the stop-signal task, including stop-signal reaction time (SSRT) as a measure of response inhibition, while undergoing functional magnetic resonance imaging. SDIs had impaired response inhibition accompanied by hypoactivation in the ventrolateral prefrontal cortex (PFC). In addition, they demonstrated hypoactivation in the anterior cingulate when failing to stop. In contrast, no hypoactivations were noted in their unaffected SIBs. Rather, they exhibited increased activation in the dorsomedial PFC relative to controls, together with inhibitory performance that was intermediate between that of the stimulant group and the healthy CT group. Such hyperactivations within the neurocircuitry underlying response inhibition and control are suggestive of compensatory mechanisms that could be protective in nature or could reflect coping with a pre-existing vulnerability, thus expressing potential aspects of resilience. The functional activation associated with response inhibition and error monitoring showed differential patterns of results between SDIs and their unaffected first-degree relatives, suggesting that the proposed endophenotype does not generalize to functional brain activity.